Hippocampus and amygdalar volumes in patients with obsessive-compulsive personality disorder - Gurok, Mehmet Gurkan; Korucu, Tuba; Kilic, Mehmet Caglar; Yildirim, Hanefi; Atmaca, Murad (Elsevier Sci Ltd, 2019)
Objectives: Moving from the point that there might be an association between the neuroanatomy of obsessive-compulsive disorder (OCD) and obsessive-compulsive personality disorder, we decided to examine the volumes of hippocampus and amygdala of patients with obsessive-compulsive personality disorder, which was previously evaluated in OCD patients by us. Methods: Volumes of the hippocampus, and amygdala were measured by magnetic resonance imaging (MRI) in patients with obsessive-compulsive personality disorder and healthy control subjects. Manual tracing was used. Results: We detected that the mean left and right sides of hippocampus and amygdala volumes of the patients with obsessive-compulsive personality disorder were smaller than those of the healthy controls. Conclusion: Consequently, our present results suggest that hippocampal and amygdalar structural abnormalities may be related to the neuroanatomy of obsessive-compulsive personality disorder. However, it is required novel studies with larger sample. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: MRI; Obsessive-compulsive personality disorder; Hippocampus; Amygdala; Volumes